Angola: An unacceptable reality of poverty and inequality (Research, Society and Development, 2024)
Angola is not inherently a poor country, but rather has been affected by a history of slavery and civil conflicts, generating injustice, inequality and a large portion of the population living in precarious conditions. The limitations faced, such as the lack of access to essential social rights for the majority of the population, together with inequalities in economic and social opportunities, are the main drivers of poverty. Placing the country in last position among the PALOP in the 2023 Legatum Prosperity Index and occupying the penultimate position in relation to its neighboring countries. This study seeks to analyze the trajectory and characteristics of poverty and inequality in Angola, adopting Amartya Sen's approach to combat deprivation and promote individual freedoms as a way to reduce poverty. While it is not feasible to address all social deprivations in this limited space, we focus on fundamental social rights such as education, health and employment. We conclude that strategies must prioritize not only economic growth, but also the promotion of individual freedoms and skills, facilitating access and use of social policies for the most vulnerable populations, breaking down social barriers.